Assessment of reporting completeness in acupuncture studies on patients with functional constipation using the STRICTA guidelines. (November 2022) - Wei, Chao; Xu, Yue; Deng, Xiangui; Gao, Shudi; Wan, Xuemei; Chen, Jing
Abstract: Objective: To evaluate the completeness of reporting of acupuncture interventions in trials for functional constipation (FC) following the STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) guidelines. Methods: We searched eight databases for all published trials, including clinical trials, pilot/feasibility studies, observational studies, and case studies, for acupuncture in patients with FC up to June 31, 2021. The completeness of reporting was evaluated using the STRICTA guidelines. Results: Finally, 99 studies were included and analysed based on the latest STRICTA guidelines. Out of the 17 analysed STRICTA sub-items, only five were found to be appropriately reported in more than 90% of the trials, while five were completely reported in less than 30%. Conclusions: The reporting completeness of acupuncture trials for FC in accordance with STRICTA guidelines is moderate, with poor guideline adherence for several items. Clinical trial reports should be further improved in accordance with STRICTA guidelines to enhance the completeness of evidence. There is also a need to explore the underlying reasons as to why the authors did not report these items and to develop strategies for improving guideline compliance. Highlights: FC brings considerable clinical and economic burden to patients. The completeness of reporting is crucial to ensure the suitability and reproducibility of acupuncture clinical trials. The adherence to STRICTA guidelines of acupuncture trials for FC is suboptimal.